2016
DOI: 10.1007/s41207-016-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PAH removal efficiency in an artificial soil amended with different types of organic wastes

Abstract: The removal of polycyclic aromatic hydrocarbons (PAHs) from a spiked OECD (Organisation for Economic Co-operation and Development) artificial soil was investigated. Laboratory-scale thermally insulated bioremediation reactors were used to implement biostimulation strategy of composting. The selected PAHs included anthracene, chrysene, benzo(k)fluoranthene, and benzo(a)pyrene with an initial concentration of 658 mg of USEPA 16 PAHs kg -1 soil (d/w). The contaminants' removal was improved by amending the contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Chemical surfactants are used in bioremediation to increase the apparent solubility of PAHs in groundwater (Lamichhane et al, 2017;Lukić et al, 2016), but the bioavailability of PAHs trapped in chemical surfactant micelles is not insured (Shao et al, 2017) and the toxicity of the chemical surfactant itself could lead to a decrease in the biodegradation process. For example, addition of SDS in high concentrations (100 and 500 mg/kg) increased the PAHs concentration in water , but it decreased the biodegradation of PAHs due to the toxicity of the SDS towards the bacterial strains (Deschênes et al, 1995;Lima et al, 2011).…”
mentioning
confidence: 99%
“…Chemical surfactants are used in bioremediation to increase the apparent solubility of PAHs in groundwater (Lamichhane et al, 2017;Lukić et al, 2016), but the bioavailability of PAHs trapped in chemical surfactant micelles is not insured (Shao et al, 2017) and the toxicity of the chemical surfactant itself could lead to a decrease in the biodegradation process. For example, addition of SDS in high concentrations (100 and 500 mg/kg) increased the PAHs concentration in water , but it decreased the biodegradation of PAHs due to the toxicity of the SDS towards the bacterial strains (Deschênes et al, 1995;Lima et al, 2011).…”
mentioning
confidence: 99%
“…This observation corroborate previous finding which demonstrated that carboxylation on C-1 of fluorene which yielded fluorene-1-carboxylic acid as a metabolite increased acute toxicity in zebrafish than its parent compound (fluorene) (Kim et al 2020 ). It is worth noting that the variation in log CFU/mL of the primary decomposer and the tertiary consumer percentage cell viability per each PAHs degradation product has revealed that toxicity is not a function of contaminant concentrations but its molecular structure and exposure time-dependent (Lukić et al 2016 ). Also, the most probable explanation for the observed cell viability exceeding 100% in the ABTS degradation products exposed cells further attests to the non-toxic nature of these degradation products with the possibility of the cell line utilizing one or more metabolites, leading to the enhanced metabolic activity of the cell line.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the higher diversity soils, the effect of inorganic nutrient amendments was negative compared to untreated soils, despite the fact that the fertilizer‐treated soils had initially more bioavailable P and N. This inconsistent effect from inorganic fertilizer addition could be ascribed to the rapid nutrient metabolization that occurred in the higher diverse soil, in which the pool of added nutrients was rapidly depleted and thus possibly made unavailable to the pyrene‐degrading microbial subcommunity in the critical first few weeks of exposure to pyrene. Conversely, in less diverse soils, inorganic amendments took longer to be metabolized, increasing nutrient availability for pyrene degraders (Sarkar et al ., 2005; Kalantary et al ., 2014; Lukić et al ., 2016), which in turn had a boosting effect on the biodegradation rate (Leff et al ., 2015; Zhu et al ., 2016; Xue et al ., 2018; Sivaram et al ., 2019). Consistent with these findings, inorganic nutrient addition in the low diversity soil supported a unique assemblage of bacterial indicator taxa with known bioremediation abilities, such as members of Proteobacteria and Firmicutes (Venail and Vives, 2013; Ren et al ., 2016; Zada et al ., 2021), while the differentiation of the indicator community in nutrient‐amended samples was relatively weaker in the high diversity soil.…”
Section: Discussionmentioning
confidence: 99%